Sources, levels and relative bioavailability of zinc in finished performance of beefcattle in feedlots (Research, Society and Development, 2020)
The objective was to evaluate sources and levels of zinc in non-castrated cattle, with an average age of two years, finished in confinement without performance and zinc bioavailability in animals randomly distributed in 5 groups, using: Control Diet (30 mg Zn / kg of dry material ingested (MSI)); 100% ZnMet (Zn-methioninecomplex, providing more than 60 mg Zn / kg MSI); 200% ZnMet (90 mg Zn / kg MSI); 200% ZnSO4 (zinc sulfate, providing 90 mg Zn / kg MSI); Injectable Zn (Zn glycinate, providing 125.5 mg of Zn with each application, administered at 28-day intervals). The average daily weight gain (GMD) and feed conversion (AC) were higher for the group that received 200% ZnMet, followed by injectable Zn in the first 28 days of confinement, showing a reduction in value in other periods. For supplementation with organic Zn, the animals that responded to the immediate weight gain, still reached reduced the same weight as the diets that meet the minimum usage. The bioavailability of the sources and the levels were applied through the atomic absorption spectrophotometry method, through there moval of Zn through the perforations, the concentration of this element in the muscle, leather and liver, as well as in the treatment of the liver. Feed Conversion in the initial phase of confinement is more efficient with the intake of organic zinc. The bioavailability of zinc is affected by the form of administration. Injectable zinc is more concentrated in the skin and ingested is more concentrated in the liver. The liver has a greater weight in animals supplemented with dietary zinc or injectable. In the final phase of confinement, high intakes of zinc increase and reduced zinc in the stool.